Penggunaan Model Pembelajaran Direct Instruction untuk Mengingkatkan Hasil Belajar Siswa pada Pelajaran Ilmu Pengetahuan Sosial - Cahyo, Edo Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
This study aimed to improve students' learning outcomes of Social Studies by using Direct Instruction Learning Model. The Classroom Action Research was performed by engaging students of V A Madrasah Ibtidaiyah Muhammadiyah 1 Banjarsari. Data collection technique were carried out using test and non-test techniques. The study revealed that the students' score increased from 78.17 up to 85.43. Furthermore, the use of Direct Instruction Learning Model simplified teachers for handling the learning process.